Urban heat island‐induced increases in evapotranspirative demand. Issue 2 (28th January 2017) - Zipper, Samuel C.; Schatz, Jason; Kucharik, Christopher J.; Loheide, Steven P.
Abstract: Although the importance of vegetation in mitigating the urban heat island (UHI) is known, the impacts of UHI‐induced changes in micrometeorological conditions on vegetation are not well understood. Here we show that plant water requirements are significantly higher in urban areas compared to rural areas surrounding Madison, WI, driven by increased air temperature with minimal effects of decreased air moisture content. Local increases in impervious cover are strongly associated with increased evapotranspirative demand in a consistent manner across years, with most increases caused by elevated temperatures during the growing season rather than changes in changes in growing season length. Potential evapotranspiration is up to 10% higher due to the UHI, potentially mitigating changes to the water and energy balances caused by urbanization. Our results indicate that local‐scale land cover decisions (increases in impervious cover) can significantly impact evapotranspirative demand, with likely implications for water and carbon cycling in urban ecosystems. Key Points: Urban heat island (UHI) increases reference evapotranspiration (RET), with consistent response to impervious cover across years RET and vapor pressure deficit changes are explained by increased air temperature, with minimal impact of decreased air moisture content. Changes in within‐season RET are more important than UHI‐induced lengthening of growing season